Penerapan Sistem Pengolahan Air Bersih Otomatis Berbasis Mikrokontroller di PDAM Kabupaten Lamongan - Affan Bachri; arief budi laksono (Universitas Islam Lamongan, 2020)
Based on development of modern technology of clean water, PDAM Lamongan follows and exerts the sophisticate tools. It helps the employees’ occupation out automatically. It’s a reason that the researcher take one of the fields, namely the automatic water control system which is discuss about work control system. The purpose of this research is in order to processing clean water in PDAM Lamongan by using a microcontroller can be simple and efficient. The first trial by using composer of Prototype components, which are consists of ultrasonic sensors, sensor turbidity meters, LCDs, flowmeter. This trial is in order to ensure that the tools can work and function properly. Based on the trial and analyze the data, the reasons are turbidity meter can worked well which could be shown through an LCD which integrated with Arduino Uno. So, the lowest value was <5NTU and the highest value was> 5NTU. The other sensors, such as ultrasonic sensors, flow meters can be function properly. In the future, those tools are expectable to develop by increasing remote control system to far distance in order to control easily and efficiently